Identification of molecular glues of the SLP76/14-3-3 protein-protein interaction - Soini, Lorenzo; Redhead, Martin; Westwood, Marta; Leysen, Seppe; Davis, Jeremy; Ottmann, Christian (RSC medicinal chemistry, 2021)
The stabilisation of protein-protein interactions (PPIs) through molecular glues is a novel and promising approach in drug discovery. In stark contrast to research in protein-protein inhibition the field of stabilisation remains underdeveloped with comparatively few examples of small-molecule stabilisers of PPIs reported to date. At the same time identifying molecular glues has received recent sustained interest, especially in the fields of targeted protein degradation and 14-3-3 PPIs. The hub-protein 14-3-3 has a broad interactome with more than 500 known protein partners which presents a great opportunity for therapeutic intervention. In this study we have developed an HTRF assay suitable for HTS of the 14-3-3/SLP76 PPI and have completed a proof of concept screen against a chemically diverse library of 20 K molecules. The adaptor protein SLP76 has been reported to interact with 14-3-3 proteins downstream of the TCR playing an important role in mediating its own proteasomal degradation. We believe that stabilisation of this PPI could be exploited to potentiate degradation of SLP76 and therefore inhibit TCR signalling. This would represent an interesting alternative to other approaches in the field of targeted protein degradation. Here we disclose 16 novel stabilisers of the 14-3-3/SLP76 PPI across multiple different chemotypes. Based on the early results presented here we would recommend this approach to find molecular glues with broad applicability in the field of 14-3-3 PPIs. The stabilisation of protein-protein interactions (PPIs) through molecular glues is a novel and promising approach in drug discovery.